Building Bridges: Universitas Multimedia Nusantara's Experience in Strengthening Academic Relationships through a Social Community Media Approach - Sugiarto, Jonathan Christian Adif; Istiono, Wirawan (Journal of Information System and Informatics, 2023)
Universitas Multimedia Nusantara has thousands of academicians and several academic or non-academic organizations. Some of these things allow the potential for increased social relationship connections between the academic community and the intensity of receiving and disseminating information, especially for students. Through a survey of students, there are examples of confirmed problems regarding the receipt and dissemination of information such as the lack of exposure of student work, the location of wall magazines that are difficult to find, information on student emails that are less relevant, time-consuming searches for coursework respondents, and the number of social media accounts of organizations that must be searched on different social media platforms to get information. Therefore, the design and development of a social community media website utilizing the Rapid Application Development method, a rapid prototype system development model with the stages of planning, design workshop, and implementation. The focus of the research is the backend system. The backend system design utilizes draw.io to create flowcharts and supabase schema for entity relationship diagrams, while the system development utilizes javascript with next js as the system development tool while system development utilizes javascript with next js as a framework and supabase as the system database. Backend media website backend of the social community media website was successfully designed and built and received User Acceptance Testing results with an acceptance rate of 88.08% for the perceive usefulness and 88.67% for the perceive satisfaction variable, which means that users strongly agree that the function of the social community media website system has fulfilled the two elements of the variable.